Assessing the Correlation between Camera Angle and the Accuracy of Elevation Measurements Derived from UAV-Photogrammetry: - - Helik Susilo; Dandung Novianto; Trias Rahardianto; Dyah Ayu Rahmawati Cupasindi; Muhamad Fajar Subkhan; Supiyono; Fuji Asema (Universitas Negeri Padang, 2025)
Elevation measurement is essential for various applications, including construction engineering, monitoring land subsidence, maintaining infrastructure, etc. A conventional method for elevation measurement involves terrestrial surveying using a Total Station instrument. However, this method can be time-consuming and requires a considerable number of personnel. Unmanned Aerial Vehicle (UAV) photogrammetry method offers a more efficient solution for determining elevation. This method utilizes UAVs equipped with camera sensors to capture aerial photos. In this research, aerial photos were taken using three different camera angle configurations: nadir (90°), oblique (65°), and oblique (45°). The elevation points derived from the UAV photogrammetry data were compared with the elevation measured by the Total Station. The analysis showed that the nadir (90°) camera angle configuration had the lowest Root Mean Square Error (RMSE) at 0.0471 meters, followed by the oblique (65°) configuration with RMSE of 0.0508 meters, and the obliqu (45°) configuration with RMSE of 0.1399 meters. According to the t-test, the elevations derived using the UAV photogrammetry method were not significantly different from the elevations measured with the Total Station.